International Market Development Strategies for MSMEs: Case Studies in the Southeast Asian Region - Mohammad Amin; Sudarmiatin Sudarmiatin (JURNAL RISET MANAJEMEN (JURMA), 2024)
MSMEs play a crucial role in ASEAN's economic growth; nonetheless, only 15% have achieved sustained entry into foreign markets, highlighting a deficiency in internationalisation capabilities. This study seeks to examine the impact of digital competence, market intelligence, and international networks on the internationalisation performance of MSMEs in the ASEAN region. A quantitative technique employing a cross-sectional explanatory study design was utilised to collect data from 250 MSME exporters across five principal ASEAN nations (Indonesia, Malaysia, Thailand, Vietnam, and Singapore) via a structured survey. Multiple regression analysis indicated that digital capacity, market knowledge, and international networks positively and significantly influence MSME internationalisation performance. The findings underscore the necessity of a cohesive strategy for MSME capability development to improve the efficacy of international expansion, while offering strategic direction for policymakers in formulating programs to facilitate MSME internationalisation in the ASEAN area.